2018
DOI: 10.3324/haematol.2018.205252
|View full text |Cite
|
Sign up to set email alerts
|

CD123 expression patterns and selective targeting with a CD123-targeted antibody-drug conjugate (IMGN632) in acute lymphoblastic leukemia

Abstract: The potential of CD123-targeted therapies in acute lymphoblastic leukemia/lymphoma remains largely unexplored. We examined CD123 expression levels in a large cohort of patients with acute lymphoblastic leukemia/lymphoma and assessed the in vitro impact of IMGN632, a conjugate of CD123-binding antibody with a novel DNA-alkylating payload. CD123 expression on leukemic blasts was surveyed using multicolor/multiparameter flow cytometry. The in vitro effect of IMGN632 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
(43 reference statements)
2
37
0
1
Order By: Relevance
“…Sreejesh et al 26 reported 1 case of B-ALL with CD5 expression, indicating that CD5 expression is a poor prognostic marker in patients below 18 years of age. Angelova et al 27 reported on 183 patients with B acute lymphoblastic leukemia/lymphoma. The expression of CD123 in B acute lymphoblastic leukemia/lymphoma is prevalent (164/183; (89.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Sreejesh et al 26 reported 1 case of B-ALL with CD5 expression, indicating that CD5 expression is a poor prognostic marker in patients below 18 years of age. Angelova et al 27 reported on 183 patients with B acute lymphoblastic leukemia/lymphoma. The expression of CD123 in B acute lymphoblastic leukemia/lymphoma is prevalent (164/183; (89.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed in subsequent studies, showing also that CD123 overexpression in B-ALL associates with hyperdiploid genotype [84]; furthermore, CD123 is clearly expressed at higher levels in B-ALL blasts than in normal B-lymphoid progenitors/precursors [85,86]. More recently, Angelova et al have performed a large screening of CD123 expression on a large set of ALLs, showing that CD123 expression was more prevalent in Philadelphia chromosome-positive patients than in Philadelphia chromosome-negative patients [87]. Importantly, Liu et al reported the existence of a negative correlation between CD123 expression on B-ALL blasts and both disease-free and overall survival [88].…”
Section: Introductionmentioning
confidence: 99%
“…The number of CD123 molecules expressed on various cell populations are indirectly reflected in the intensity of fluorescence detected, which is typically expressed as median fluorescence intensity (MFI). Such intensity is normalized against background fluorescence and/or control cell populations [ 22 ]. Furthermore, by employing carefully selected lineage and maturation-associated markers, CD123 expression on neoplastic cells can be clearly distinguished from that on other cell populations within a given sample.…”
Section: Principles Of Laboratory Evaluation Of Cd123mentioning
confidence: 99%
“…CD123 is frequently overexpressed in B-ALL. Angelova and colleagues [ 22 ] conducted a large study in which CD123 expression was evaluated by FC in various subsets of B-ALL and T-ALL. They demonstrated CD123 overexpression in 96.6% of Ph-positive and 86.3% of Ph-negative B-ALL.…”
Section: Cd123 Expression In Hematologic Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation